Nationalism in the light of Said Nursi Badiuzzaman and his framework for social solidarity - Abdul Rahim, Adibah; Akhmetova, Elmira (Department of Islamic Thought and Civilization, School of Social Sciences and Humanities,University of Management and Technology, 2019)
For the past few centuries, the impact of nationalism had been discussed widely by scholars both in the Western and the Muslim world in various perspectives. Some authors claimed that nationalism had caused a lot of conflicts and wars among the nations. On the other hand, some others argued that nationalism was a binding force which stabilized the fragmented territories of nation-states with the sentiments of nationalism. This paper attempts at analyzing Badiuzzaman Said Nursi’s approach towards the issue of nationalism. He did not merely criticize nationalism; he offered a better way through his approach to a sociology of Islam. Nursi explains and advocates for positive forms of social solidarity and cohesion that elevate a group of people to noble action, and provides the Islamic grounding for that position. Within the various conflicts afflicted around the world today, Nursi’s ideas of nationalism and social solidary are seen relevant and necessary in context.